Cambodia Economic Update - Weathering the Oil Price Shock : Special Focus - Post-Pandemic Supply Chain Disruptions : Strategies to Reduce Logistics Costs - World Bank (Washington, DC : World Bank, 2022)
Cambodia is now weathering an oil price shock, just as the economy had started to recover amid a rollback of Coronavirus (COVID-19)-related restrictions. Negative impacts of the oil price shock are amplified by Cambodia’s already large external imbalances. Rising food and energy prices have eroded household purchasing power. International oil price increases are passing directly through to domestic prices. Higher commodity prices triggered by the war in Ukraine are expected to lead to sizable fiscal impacts. Meanwhile, the “living with COVID-19” strategy has enabled a reopening of the economy since late last year. The economic recovery remains uneven. Traditional growth drivers, especially the garment, travel goods, and footwear manufacturing industries, continue to expand. Rising inflationary pressures are posing serious policy challenges for the Cambodian authorities. To this end, it is crucial for the central bank to continue to be committed to maintaining exchange rate stability. For the government, it is important to avoid creating excess aggregate demand, which might trigger undue domestic inflationary pressures on top of the imported inflation. The prospect of a protracted period of high inflation and a sharp increase in global interest rates has significant implications for Cambodia, whose economy is highly dollarized.